Inflammatory-Metal Profile as a Hallmark for COVID-19 Severity During Pregnancy - Vásquez-Procopio, Johana; Espejel-Nuñez, Aurora; Torres-Torres, Johnatan; Martinez-Portilla, Raigam Jafet; Espino Y. Sosa, Salvador; Mateu-Rogell, Paloma; Ortega-Castillo, Veronica; Tolentino-Dolores, Maricruz; Perichart-Perera, Otilia; Franco-Gallardo, José Osman; Carranco-Martínez, José Alberto; Prieto-Rodríguez, Scarleth; et al. (Frontiers in Cell and Developmental Biology, 2022)
Pregnancy makes women more susceptible to infectious agents; however, available data on the effect of SARS-CoV-2 on pregnant women are limited. To date, inflammatory responses and changes in serum metal concentration have been reported in COVID-19 patients, but few associations between metal ions and cytokines have been described. The aim of this study was to evaluate correlations between inflammatory markers and serum metal ions in third-trimester pregnant women with varying COVID-19 disease severity. Patients with severe symptoms had increased concentrations of serum magnesium, copper, and calcium ions and decreased concentrations of iron, zinc, and sodium ions. Potassium ions were unaffected. Pro-inflammatory cytokines IL-6, TNF-α, IL-8, IL-1α, anti-inflammatory cytokine IL-4, and the IP-10 chemokine were induced in the severe presentation of COVID-19 during pregnancy. Robust negative correlations between iron/magnesium and zinc/IL-6, and a positive correlation between copper/IP-10 were observed in pregnant women with the severe form of the disease. Thus, coordinated alterations of serum metal ions and inflammatory markers – suggestive of underlying pathophysiological interactions – occur during SARS-CoV-2 infection in pregnancy.